The backwater boats of Kerala: identity, place and the world of Munruthuruthu. - Jesse Ransley
Drawing on ethnographic research in Munruthuruthu, a boat building village in Kerala, south- western India, this paper discusses the study of ‘traditional’ boats as a means to explore the multivalent relations between people and their watery world. The research it draws on addresses boats as a lens through which the web of meanings and interactions that enmesh them can be illuminated. Thus, study of the construction methods and social relationships involved in making boats, the daily journeys they make and the work they are involved in, reveals the production and negotiation of identities, discloses perceptions of environment and, ultimately, how people, places and things are constituted through everyday work practices, technical skills and all the other relational, embodied, habitual activities of life. This paper focuses on one part of a kettuvallam, or ‘tied boat’, to draw out some of these ideas. In doing so, it suggests that by examining the material construction of boats a ‘traditional boat study’ can also ask what boats reveal about the world in which they are created.